2021
DOI: 10.1186/s40878-020-00217-x
|View full text |Cite
|
Sign up to set email alerts
|

British and Japanese international retirement migration and creative responses to health and care challenges: a bricolage perspective

Abstract: Most research on international retirement migration has focused on the Western context and the motivations and lifestyle choices of migrants when they are healthy. This paper instead explores how British retirees in Spain and Japanese retirees in Malaysia respond to declining health and increasing care needs through bricolage as they begin to ‘age in place’. The paper combines qualitative interviews, focus groups and observations collected by the authors from 215 British and Japanese international retirement m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Hall and Hardill (2016) suggested that older British people in Spain retained a strong dependence on the United Kingdom, particularly regarding health care. This is similar to US retirement migrants in Mexico, who often traveled to the United States to make use of their medical insurance coverage (Lardiés-Bosque, Guillén, and Montes-de-Oca 2016), and Dutch retirement migrants in Spain, who often adapted their mobility patterns to ensure that they retained access to their origin country's health care systems (Gehring 2016(Gehring , 2017, resulting in transnational health care practices (Gehring 2016;Hall, Ono, and Kohno 2021;Kahveci, Karacan, and Kosnick 2020;Toyota and Xiang 2012).…”
Section: Health and Well-beingmentioning
confidence: 81%
“…Hall and Hardill (2016) suggested that older British people in Spain retained a strong dependence on the United Kingdom, particularly regarding health care. This is similar to US retirement migrants in Mexico, who often traveled to the United States to make use of their medical insurance coverage (Lardiés-Bosque, Guillén, and Montes-de-Oca 2016), and Dutch retirement migrants in Spain, who often adapted their mobility patterns to ensure that they retained access to their origin country's health care systems (Gehring 2016(Gehring , 2017, resulting in transnational health care practices (Gehring 2016;Hall, Ono, and Kohno 2021;Kahveci, Karacan, and Kosnick 2020;Toyota and Xiang 2012).…”
Section: Health and Well-beingmentioning
confidence: 81%
“…Whilst the rights of those who moved to another EU country (and became legally resident) by 31 December 2020 have been secured under the Withdrawal Agreement, the same rights will not be available to those who move from January 2021. Whilst all of the interviewees in this study were legally resident in Spain, other research indicates that some IRMs do not register (Hall et al ., 2021) and so will have minimal rights to both residency and welfare post-Brexit, leaving them in a more precarious state when they need care. This research was undertaken before the COVID-19 pandemic, but it is also likely that the pandemic has exacerbated or introduced precarity in the lives of IRMs.…”
Section: Discussionmentioning
confidence: 99%
“…Bradby et al, 2019;Phillimore et al, 2019Phillimore et al, , 2021a. Within this special issue we offer examples of wide-ranging methodological approaches some of which engage with large datasets (Igarashi and Laurence, 2021) or rely on working within places for the long durée (Hall et al, 2021;Drnovšek Zorko and Debnár, 2021;Wessendorf and Farrer, 2021).…”
Section: Superdiversity and Superdiversificationsmentioning
confidence: 99%
“…Our final papers bring a new perspective to migration research. The first by Hall et al (2021) looks outwards at the emigration of 'third age' migrants from the UK to Spain and Japan to Malaysia. In both contexts, migrants tended to move into already established ethnic communities and maintain transnational ties with the homeland.…”
Section: Structure Of the Special Issuementioning
confidence: 99%